(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
Didactic content knowledge has been an inexhaustible source of research in recent decades. This is because the teacher requires disciplinary knowledge, and knowledge about how to teach that disciplinary knowledge. Therefore, the objective of this research is to identify the relationships that occur between the didactic knowledge components of the content in practical laboratory work through a systematic literature review. A search and selection were made in national and international journals from the Scopus, Redalyc, Google Academic and Eric databases. 56 articles were identified that address the CDC, in which the most obvious category is to present the CDC as a line of teacher training, followed by perceiving the CDC as a way of addressing the problem of teaching-learning processes and the CDC is identified as emerging research line in science teaching. 52 articles that address practical work, in which didactic involvement is evidenced as the most reported approach, in addition to the perception of practical work as research and learning process. The didactic knowledge of the content and the practical laboratory work have been consolidated as areas of didactic research, being important fields in the teacher training processes. The trends identified are the experiences in the classroom, the didactic implications, the reflection processes of the pedagogical practice and the consolidation of research processes.